The Role Of Entrepreneurial Resilience And Entrepreneurial Self-Efficacy On Entrepreneurial Intention On Students In Padang City - Emrizal, Emrizal; Primadona, Primadona (International Journal of Science, Technology & Management, 2023)
This study aims to see the extent to which the role of entrepreneurial resilience and entrepreneurial self-efficacy on entrepreneurial intention of students in the city of Padang. This research was conducted by collecting data from 273 student respondents in the city of Padang. The data were processed by multiple regression analysis using the SPSS program. The results of the study indicate that there is a positive and significant effect of entrepreneurial resilience and entrepreneurial self-efficacy variables on entrepreneurial intention, either partially or simultaneously. This research is novel because there is still limited research on entrepreneurial intention associated with entrepreneurial resilience and entrepreneurial self-efficacy, especially in disaster-prone areas.